Austinotheres angelicus (Lockington, 1877): the correct name for the symbiotic crab Juxtafabia muliniarum sensu Cabrera-Peña et al. (2001) (Crustacea, Brachyura, Pinnotheridae) - Campos González, Ernesto (2014)
The taxonomic identity of the symbiotic crabs Juxtafabia muliniarum sensu Cabrera-Peña et al. (2001) was revised. The morphology of these specimens, collected in the estuary of Punta Morales, Pacific coast of Costa Rica, in the oyster Saccostrea palmula did not agree with J. muliniarum but concurs well with topotypes and voucher material of Austinotheres angelicus from the Gulf of California, Mexico. Austinotheres angelicus belongs to the subfamily Pinnotherninae sensu Campos, 2009, and the morphology of A. angelicus supports its close relationship with Bonita mexicana and Enigmatheres canfieldi. The presence of a soft and thin carapace colored with deep chocolate brown with dark purple tones, a conspicuous rotuberance in the basal antennal article, a third maxilliped with an ischio-merus fused with its inner margin angled, a carpus larger than the propodus, and a digitiform and small dactylus subdistally inserting on the ventral margin of the propodus are diagnostic features for A. angelicus. These characteristics separate this species from other pinnotherid crabs from the entire Pacific Ocean